Creating Added Value for the On Tai Sub-District Community Enterprises Based on Creative Marketing, Brand, Identity and Storytelling - Chum-Un, Manop (Community and Social Development Journal, 2021)
This research focused on creating added value for the community enterprises of the On Tai sub-district based on creative marketing, brand identity, brand positioning, and storytelling. The research involved the application of the mixed method as the qualitative research instrument, which consisted of in-depth interviews and group discussions, while the quantitative instrument consisted of questionnaires administered to 400 tourists and 20 experts within the On Tai community context. The content and descriptive statistics were for data analysis. The findings of creating value-added from creative marketing showed that the community must create a common experience for tourists to learn the spirit of the place and experience the genuine charm of the community, and the community must develop souvenir products for distribution and sale on community tourist routes. Branding results indicated that a brand portfolio would include a family brand under On Tai with the logo of three fishes moving clockwise in a circle with a floral in the center and a slogan that describes the identity of the community as the land of watershed fertility and peacefulness. The market positioning was to describe the community as the land of peace with various tourist attractions, and the products containing a quality of wisdom. The result of identity creation determined by the Delphi technique showed that the most notable physical characteristics were the landscape and natural environment, with a mean score of 4.10, the most notable local activity was the lifestyle with a mean of 3.95, and qualities of symbolism and wisdom were learning centers and service centers with a mean of 3.90. Finally, the storytelling finding showed that the characters branded the place with the family name “On Tai” which was derived from the location of the On Tai community.